Half of 57 is 28.5. Hoped I helped. :)
Answer:
Hope this will help you and hope you understand my handwriting
Answer:
16x5+6x4
Step-by-step explanation:
(2x(3+5)+6)(x4)
=(2x(3+5)+6)(x4)
=(2x(3+5))(x4)+(6)(x4)
=16x5+6x4
<em>For</em><em> </em><em>the</em><em> </em><em>attached</em><em> </em><em>image</em><em>,</em><em> </em><em>note</em><em> </em><em>that</em><em> </em><em>slope</em><em> </em><em>is</em><em> </em><em>the</em><em> </em><em>same</em><em> </em><em>thing</em><em> </em><em>as</em><em> </em><em>gradient</em><em>.</em>
1) y = 2x + 4
2) Substituting in x = 1 and y = 1,
1 = 4(1) + c
1 = 4 + c
c = -3
So, the equation is y = 4x - 3
Answer:
<h2>4 + 3x</h2>
Step-by-step explanation:
The product of three and a number x: 3 · x = 3x
The sum of four and the product of three and a number x:
4 + 3x